Dairy curd coagulated by a plant extract of Calotropis procera: Role of fat structure on the chemical and textural characteristics. (March 2018) - Issa Ado, Rayanatou; Lopez, Christelle; Lechevalier, Valérie; Elhadji Gounga, Mahamadou; Robert, Benoit; Harel-Oger, Marielle; Garric, Gilles; Grongnet, Jean-François; Gaucheron, Frédéric
Abstract: Milk is often subjected to technological treatments which have impacts on the structure of milk constituents and the characteristics of rennet curds. In this paper, the influence of the dairy fat structure on the biochemical and textural characteristics of curds coagulated by an extract of Calotropis procera leaves was studied. Standardized milks were reconstituted with the same contents in protein (35 g·kg − 1 ) and fat (35 g·kg − 1 ) but with different structures of fat i.e. homogenized anhydrous milk fat (HAMF), homogenized cream (HC) and non-homogenized cream (NHC). As expected, the size distributions of fat globules in the different milks were different. After their coagulations by the plant extract, the physico-chemical characteristics of the curds and respective wheys were determined. No difference was observed in the coagulation time between the three milks but the whey removed more quickly from HAMF and HC curds than NHC-curd. The biochemical analyses of curds revealed a lower content in dry matter and fat in the NHC-curd compared to HAMF- and HC-curds. Otherwise, the NHC-whey exhibited the highest amount of fat. Observations by confocal microscopy showed that the fat globules were homogenously distributed and well trapped in the protein networks of HAMF- and HC-curds. In the NHC-curd, the fat globules were located in whey pockets, with less connectivity with the protein network. The textural analysis showed that the NHC-curd was more elastic, soft and adhesive than HAMF- and HC-curds. Homogenization significantly reduced the loss of fat during cheese manufacturing and conferred specific textural characteristics to the curds coagulated by an extract of Calotropis procera . Graphical abstract: Highlights: Homogenization at 100 + 10 Pa modifies the interactions between fat and protein in milk and dairy curds. Homogenization leads to a better recovery rate of fat in curds manufactured using Calotropis procera extract as coagulant. Fat structure impacts on the biochemical and textural characteristics of curds coagulated with Calotropis procera extract.